Phenotypic Characteristics of Hyperacusis in Tinnitus - Schecklmann, Martin (2014)
Background: Many people with tinnitus also suffer from hyperacusis. Both clinical and basic scientific data indicate an overlap in pathophysiologic mechanisms. In order to further elucidate the interplay between tinnitus and hyperacusis we compared clinical and demographic characteristics of tinnitus patients with and without hyperacusis by analyzing a large sample from an international tinnitus patient database. Materials: The default dataset import [November 1st, 2012] from the Tinnitus Research Initiative [TRI] Database was used for analyses. Hyperacusis was defined by the question “Do sounds cause you pain or physical discomfort?” of the Tinnitus Sample Case History Questionnaire. Patients who answered this question with “yes” were contrasted with “no”-responders with respect to 41 variables. Results: 935 [55%] out of 1713 patients were characterized as hyperacusis patients. Hyperacusis in tinnitus was associated with younger age, higher tinnitus-related, mental and general distress; and higher rates of pain disorders and vertigo. In relation to objective audiological assessment patients with hyperacusis rated their subjective hearing function worse than those without hyperacusis. Similarly the tinnitus pitch was rated higher by hyperacusis patients in relation to the audiometrically determined tinnitus pitch. Among patients with tinnitus and hyperacusis the tinnitus was more frequently modulated by external noise and somatic maneuvers, i.e., exposure to environmental sounds and head and neck movements change the tinnitus percept. Conclusions: Our findings suggest that the comorbidity of hyperacusis is a useful criterion for defining a sub-type of tinnitus which is characterized by greater need of treatment. The higher sensitivity to auditory, somatosensory and vestibular input confirms the notion of an overactivation of an unspecific hypervigilance network in tinnitus patients with hyperacusis.